Annual gonad cycle of the climbing perch Anabas testudineus (teleostei anabantidae) in the Candaba wetland, Central Luzon Island, Philippines - Bernal, Rieziel Ann D. (College of Science, University of the Philippines Diliman, 2015)
Seasonal reproduction of the climbing perch Anabas testudineus in the Candaba wetland, Philippines is described. Monthly specimens were collected, gonads and viscera excised, and the gonads histologically examined. Low mean ovarian gonadosomatic index (GSI) from September to February (0.3-2.1%) increased in March (8.7%), peaked in May (10.9%), declined in June (3.3%), but increased again in July and August (5.5-8.3%). Testicular GSIs (at least 1.0%) were low from September until May, increased in June (2.5%), and then declined thereafter. Six oocyte and four spermatogenic cell development stages were observed in the gonads throughout the annual cycle. The ovary was dominated by primary growth oocytes from August to February (77-90%) but yolky oocytes comprised 15-28% of the ovary from March to July. Mature oocytes were present for the most of the year, comprising 40% of the total oocytes in March to April, peaking May (50%), but declining to 30% in June to July. Spermatozoa consistently dominated testis throughout the annual cycle, particularly in November and March (58%). Food intake in both sexes was generally low during the dry season (December to April) when gonad activity was also low, but started to increase at the onset of the wet season (May to November) when gonad activity was at its peak. Unlike in males, ovarian maturation stage significantly correlated with body size, gonad weight, amd GSI, allowing for the estimation of the minimum body size at maturity to be 113.4 mm among female climbing perch. Overall, these results demonstrate that the climbing perch gonads exhibit asynchronous development, allowing a protracted breeding season with peak gonad activity timed at the onset of the wet season concurrent with increasing food intake through the rest of the season.